Management-employee relations, firm size and job satisfaction - Aysit Tansel; Saziye Gazioglu (Institute for the Study of Labor (IZA), 2013)
This paper investigates the job satisfaction in relation to managerial attitudes towards employees and firm size using the linked employer-employee survey results in Britain. We first investigate the management-employee relationships and the firm size using maximum likelihood probit estimation. Next various measures of job satisfaction are related to the management-employee relations via maximum likelihood ordered probit estimates. Four measures of job satisfaction that have not been used often are considered. They are satisfaction with influence over job; satisfaction with amount of pay; satisfaction with sense of achievement and satisfaction with respect from supervisors. Main findings indicate that management-employee relationships are less satisfactory in the large firms than in the small firms. Job satisfaction levels are lower in large firms. Less satisfactory management-employee relationships in the large firms may be a major source of the observed lower level of job satisfaction in them. These results have important policy implications from the point of view of the firm management while achieving the aims of their organizations in particular in the large firms in the area of management-employee relationships. Improving the management-employee relations in large firms will increase employee satisfaction in many respects as well as increase productivity and reduce turnover. The nature of the management-employee relations with firm size and job satisfaction has not been investigated before.
Keywords: J28; J5; J21; D23; 330; job satisfaction; managerial attitudes; firm size; linked employer-employee data; Britain